The impact of transformational leadership style on the intention to use AI technology in Lebanese banks: The role of perceived usefulness and ease of use - Amer, Aaed J.; El-Naga, Mohamed A. Abou; Shehata, Mohamed A. (Edelweiss Applied Science and Technology, 2026)
This research investigates the impact of transformational leadership style on the intention to use Artificial Intelligence (AI) in Lebanese banks, and tests the roles of perceived usefulness and perceived ease of use. The study aims to address the gap in understanding what influences the intention to adopt AI. A quantitative, deductive research methodology was employed, utilizing a questionnaire distributed to Lebanese banking leaders. A total of 250 valid responses were collected online. Reliability and validity of the model were assessed using SPSS, while Structural Equation Modeling with AMOS was applied to evaluate the hypothesized relationships. The findings reveal that transformational leadership has a significant positive effect on perceived ease of use, but no significant impact on perceived usefulness. Additionally, perceived usefulness and perceived ease of use both exhibit a positive and significant influence on the intention to use AI. Furthermore, perceived ease of use positively affects perceived usefulness. This implies that banks can invest in hiring transformational leaders to enhance employees’ perceptions of ease of use, ultimately driving greater acceptance of AI technologies.